Influência dos modelos idealizados de ligações no dimensionamento de treliças planas de madeira - Fraga, Iuri Fazolin (Universidade Federal de São Carlos, 2020)
Throughout human history, wood has been used in numerous ways in civil construction, showing considerable advantages. Among these, sustainability and excellent mechanical properties make it a material widely used in buildings around the world, especially in countries in the Northern Hemisphere. However, in Brazil, little of its forest diversity is rationally explored in structural systems, the result of prejudices inherent to the material. Despite its reduced diffusion in the country, however, there is a widespread use of native wood on roofs of residential buildings; commercial and rural areas. The toughness and the high strength/density ratio make wood an excellent material to be used in a potentiated way in roofing structures. That is why, until today, historical structures built in the 20th century are found, currently being gradually recovered. In addition, Brazil has been going through a process of transition from timbered construction, migrating from the artisanal process to the prefabrication process. It is in these contexts that this research is inserted, contributing to the promotion of initiatives that will favor the more rational and technical use of timber in structural solutions. One of the problems that involve the design of roofing structures is related to the idealized models of analysis. In the structural design, engineers usually adopt the classic truss model, whose joints are considered to be perfectly flexible. However, in models where perfectly rigid joints are allowed (frame model), or even diagonal and vertical bars connected to continuous chords (frame-truss model), significant differences can be observed in the dimensions of the sections. Thus, prioritizing the verification of such influences, this work proposes a computational tool based on the finite element method (FEM) and in the design routines prescribed by the new draft standard of ABNT NBR 7190 (2020). In the bibliographic studies carried out, there was a scarcity of computational tools aimed at the analysis of roof structures in situations well below the ultimate strength limit, especially with a focus on design. In this way, the software, called iTruss, has elastic-linear processing, whose reliability was notorious when measured with the SAP2000® software. By setting the thickness (b), the design criterion used was the minimum height of the pieces (h) through a repetition code with a 0.10 cm step. After simulating six idealized models of a prefabricated truss, Howe type, with 12 meters span, the results showed that the sections really undergo considerable changes depending on the model adopted. The percentage divergences reached values above 40%, having as reference the classic truss model commonly accepted in the design of roof structures.
Idealized joints models influence on the design of plane timber trusses
Keywords: Estruturas de madeira; Treliças planas; Método dos elementos finitos; Dimensionamento; Timber structures; Plane trusses; Finite element method; Design; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS